A personalized path generation for an autonomous vehicle overtaking maneuver. Issue 14 (2022) - Vigne, Benoit; Orjuela, Rodolfo; Lauffenburger, Jean-Philippe; Basset, Michel
Abstract: The acceptability by a population for new technology is conditioned by its benefits and its adaptability. While an autonomous vehicle could be a nice solution as an intelligent transportation system to decrease road crashes, traffic jams, etc., the choice of a driving style (relaxed/sporty) could be a good factor of adaptability. This study presents a method to optimize a local overtaking trajectory defined as a sigmoid function integrating constraints of comfort, safety, and path continuity. An only one driving style parameter allows obtaining different paths from smooth to tight shapes respecting previous constraints. Simulations of use cases show good performance of the developed algorithm.